Joint partial equidistribution of Farey rays in negatively curved manifolds and trees - PARKKONEN, JOUNI; PAULIN, FRÉDÉRIC (Ergodic theory and dynamical systems, 2024)
We prove a joint partial equidistribution result for common perpendiculars with given density on equidistributing equidistant hypersurfaces, towards a measure supported on truncated stable leaves. We recover a result of Marklof on the joint partial equidistribution of Farey fractions at a given density, and give several analogous arithmetic applications, including in Bruhat–Tits trees.